Promoting Fast Tour and Travel Using a Marketing Booklet - Cyntia Dewi Efendi (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
Fast tour and travel is a travel agency located in Jalan Raya Lontar 259B, Surabaya, which has a unique target market who are foreigners. It hardly find their own target market and usually depend on overseas travel agencies. Therefore, a marketing booklet is an effective promotional tool that can help Fast Tour and Travel to get more foreign customers because this marketing booklet will be distributed in Universities in Surabaya which have student exchange program. This marketing booklet consists of table of content, company profile, explore Surabaya (Surabaya tourist destinations), some favourite destinations near Surabaya (Bromo, Malang, and Madura), and contact information (contact us). By having this marketing booklet, Fast Tour and Travel can get their main target market.